2021
DOI: 10.3389/ffunb.2021.671270
|View full text |Cite
|
Sign up to set email alerts
|

Site-Dependent Relationships Between Fungal Community Composition, Plant Genotypic Diversity and Environmental Drivers in a Salix Biomass System

Abstract: Soil fungi are strongly affected by plant species or genotypes since plants modify their surrounding environment, but the effects of plant genotype diversity on fungal diversity and function have not been extensively studied. The interactive responses of fungal community composition to plant genotypic diversity and environmental drivers were investigated in Salix biomass systems, posing questions about: (1) How fungal diversity varies as a function of plant genotype diversity; (2) If plant genotype identity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
1
1
0
Order By: Relevance
“…In addition, we have shown that the fungal species richness is highly dependent on the site. The site-specific composition of fungal communities was shown previously for soil, root, or foliage samples [ 72 , 73 , 74 , 75 ]. Overall, our results demonstrated that different functional tissues and the rhizosphere soil of P. sylvestris are associated with diverse fungal communities driven by a combination of climatic and edaphic factors, thereby providing insights into possible ecological responses of fungal communities to climate change in northern Europe.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, we have shown that the fungal species richness is highly dependent on the site. The site-specific composition of fungal communities was shown previously for soil, root, or foliage samples [ 72 , 73 , 74 , 75 ]. Overall, our results demonstrated that different functional tissues and the rhizosphere soil of P. sylvestris are associated with diverse fungal communities driven by a combination of climatic and edaphic factors, thereby providing insights into possible ecological responses of fungal communities to climate change in northern Europe.…”
Section: Discussionsupporting
confidence: 55%
“…The aboveground characteristics of several varieties of the genus Salix grown as short rotation coppice in monoculture are well characterized, showing some variation in traits among varieties (Bonosi et al 2013;Weih and Nordh 2002;Weih and Nordh 2005). Yet, there are only a few studies investigating their belowground traits, such as (i) root biomass (Baum et al 2018;Hoeber et al 2017), (ii) ne root composition and decomposition rates (He et al 2019), (iii) soil and root-associated fungal communities (Baum et al 2018;Hoeber et al 2021;Hrynkiewicz et al 2012;Koczorski et al 2021), (iv) dehydrogenases activities (Baum et al 2020), or (v) their impact on the increase of soil organic carbon stock (Baum et al 2020).…”
Section: )mentioning
confidence: 99%